Study of Relevance of Sharia Banking Study Program Graduates in 2019-2021 (Analysis of The Curriculum of Sharia Banking Study Program) - Anggraini, Tuti; Lathief Ilhamy, Muhammad; Perdana Indra, Ahmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This research was conducted to find out the quality of graduates, how long the wait for work is, and how the relevance of the implementation of the curriculum that has been implemented in the study program to the needs of the labor market. The latest data from the Central Statistics Agency (BPS) shows that as of August 2022, Indonesia’s unemployment rate was recorded at 5.86% of the total working-age population of 209.42 million people. What was astonishing is, of the 209.42 million people, almost 673.49 thousand (7.99%) were undergraduate graduates (S1). This tracer study is an evaluative descriptive study that seeks to describe the profile of graduates and the relevance of the curriculum materials for the Sharia Banking Program through a survey approach. From the results of this study, it is known that the waiting time for graduates to work in companies for more than 6 months is greater by 66 people, for the period before 6 months there are only 26 people and the time span above 18 months is around 24 people. Where the suitability of the field of work graduates as many as 88 people.